Data sheet on improved cowpea and groundnut varieties - Faye, Aliou; Mathew, Akinseye Folorunso (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This data sheet on improved cowpea and peanut varieties was developed as part of the AICCRA Senegal farmers' days, held from October 17 to 21, 2022, in Daga Birame, Thièle and Méouane. This document provides information on the most promising cowpea and groundnut varieties disseminated under the AICCRA Senegal project.